How Business Community Institutions Can Help Fight Corruption - Dixit, Avinash (World Bank, Washington, DC, 2014)
This paper considers the possibility of collective action by the business community to counter corruption in the award of government licenses and contracts. The analogy is with contract enforcement institutions studied by economic historians and contract law scholars. The institution in this context comprises a no-bribery norm, a community system to detect violations, and a multilateral ostracism penalty upon conviction in a community tribunal. The requirements such an institution must meet if it is to be effective are analyzed. It is shown that an institution of sufficient quality -- combining probability of correct detection and severity of punishment -- can eliminate bribery. If the private institution is not sufficiently good, then in conjunction with the state's formal apparatus it reduces the level of bribes demanded, but increases the probability of winning the license or contract through bribery. An improvement in the government's formal anti-corruption mechanism, holding the private institution constant, reduces both the level of bribes and the probability of success through bribery. The two institutions together are shown to achieve substantially better outcomes than either can on its own.